"Why bother? It's gonna hurt me": the role of interpersonal cognitive biases in the development of anxiety and depression - Belli, S (2013)
Child and adolescent mood and anxiety symptoms are common and debilitating, with long-term effects on well-being. Research presented in this thesis examines interpersonal cognitive factors in the emergence of anxious and depressive symptoms in late childhood through to early adulthood. The thesis considers this issue using three main approaches. For the first, data are presented showing that biases in the appraisals of social situations are the aspects of interpersonal cognition most closely associated with emotional symptoms. For the second, longitudinal twin data are used to examine genetic and environmental origins of these interpersonal cognitive biases and their temporal prediction of symptoms across a 2-year period. Data show that interpersonal cognitive factors are strongly influenced by non-shared environmental factors, and moreover, predict symptoms across time. The final section of the thesis comprises four studies using Cognitive Bias Modification of Interpretations (CBM-I) training methodology to show that both positive and negative interpretive biases for interpersonal information can be induced in adolescents. Positive biases are shown to persist for at least 24 hours after training, and induced positive and negative biases are shown to differentially predict anxious responses to an experimental stressor. Evidence is also provided to suggest that effects following training positive interpretive biases may transfer to other cognitive measures, namely appraisals of ambiguous emotional faces. Finally, data tentatively show that CBM-I training may be useful in reducing negative interpretations of interpersonal information made by 11-year-old children undergoing the transition to secondary school. In summary, studies in this thesis support the contribution of cognitive biases to mood and anxiety symptoms in childhood and adolescence. They further extend this knowledge by suggesting that these reflect individual-specific (non-shared) environmental risks to predict symptoms across time. These biases may also be amenable to change through training interventions, with some - albeit weak - effects on other cognitive outcomes.